Genetic Diversity of Bali Cattle Base on Two Microsatellite Loci - INRA032 and BM2113 - Maskur, Maskur; Rozi, Tapaul; Rahmajan, Rahmajan; Kasip, Lalu; Muhsinin, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Microsatellites are short tandem repeat (STR) sequences that consist of simple repeats and exhibit a high number of alleles at each genomic locus. The aim of this study was to examine genetic variation in Bali cattle and the population dynamics using microsatellite markers. Two microsatellite loci, INRA032 and BM2113 were amplified using PCR Total DNA samples from the genome of 60 Bali cattle, then The PCR products were analyzed through agarose gel electrophoresis, followed by staining with Ethidium Bromide (EtBr). The number and size of alleles that appeared on the gel, while the diversity and population dynamics were analyzed using Popgene version 1.31 and Gene Calc. In this study, The effective number of alleles for the two microsatellite loci in the Bali cattle population analyzed was 6.53, with an average of 3.27. The average PIC of the two microsatellite loci was 0.70, while the observed heterozygosity (Ho) exceeded the expected heterozygosity (He), with values of 0.975 and 0.695, respectively. This suggests an excess of heterozygosity in the population and indicates that the populations are not in Hardy-Weinberg equilibrium. The inbreeding coefficient was high, with negative Fis values of -0.38 for INRA032 and -0.43 for BM2113.